2022
DOI: 10.1186/s12913-022-08811-8
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparities in using rehabilitation services among Iranian adults with disabilities: a decomposition analysis

Abstract: Background Persons with disabilities (PWD) generally experience various barriers in using health care compared to the general population, and these problems are more worsened for those with disabilities in lower socioeconomic status. The study aimed to estimate socioeconomic inequality in using rehabilitation services (URS) in adults with disabilities in Iran. Methods This cross-sectional study was conducted at a national level in Iran. 786 PWD (ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(60 reference statements)
1
0
0
Order By: Relevance
“…Therefore, disadvantaged people in Iran are struggling more with adversities related to disability and need much more attention from policymakers. It is believed that people with disabilities may use less health services ( 34 ).This confirmed the finding of a study in Iran where it showed that the use of rehabilitation services has been concentrated among privileged Iranians ( 35 ). This requires the attention of the healthcare authorities for an equitable distribution of these services .…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, disadvantaged people in Iran are struggling more with adversities related to disability and need much more attention from policymakers. It is believed that people with disabilities may use less health services ( 34 ).This confirmed the finding of a study in Iran where it showed that the use of rehabilitation services has been concentrated among privileged Iranians ( 35 ). This requires the attention of the healthcare authorities for an equitable distribution of these services .…”
Section: Discussionsupporting
confidence: 77%